Perceptions of patients about cataract (Clinics, 2005)
OBJECTIVE: To identify in adult patients suffering from cataract the perceptions regarding the disease and its surgical treatment. MATERIALS AND METHODS: An exploratory survey was conducted among adult patients suffering from cataract and participating in a large-scale cataract management program at the University of São Paulo General Hospital in 2004. The interviews were conducted by research assistants previously trained to pose questions and record answers. RESULTS: The sample consisted of 170 men and women (43.5% and 56.5%, respectively), aged between 40 and 88 years. Of the 170 participants, 43.5% were from the State of São Paulo, 14.7% from the State of Bahia, 12.4% from the State of Minas Gerais, 5.9% from the State of Pernambuco, 1.8% from other countries, and the remaining 21.7% were from other Brazilian states. Of those who were actively working (n = 87), 43.7% had an occupational level corresponding to nonspecialized manual labor, 27.6% were in specialized manual labor jobs, 25.3% had routine nonmanual occupations, 1.1% supervised manual labor, and 2.3% had low-ranking supervision or inspection jobs over nonmanual occupations. Of those who were not actively working (n = 82), 53.6% were retired, 45.2% were housewives, and 1.2% were unemployed. Concerning conceptions about cataract, 79.0% referred to it as "a small skin fold that gradually covers the eye" and 32.4% mentioned, in addition, other conceptions. Concerning the cause, of the alternatives presented to them, 80% reported aging, 47.1% blamed "overusing the eyes in the workplace or at home", 7.1% believed they had cataract due to some kind of "spell." Of the associated answers, 94.1% referred to "blurred vision" in people suffering from cataract, 72.4% thought the person may become blind, and 66.5% believed that the patients suffering from cataract are depressed because they cannot see. Regarding surgery, 28.8% were afraid of undergoing surgery; of those, 16.3% cited with the fear of dying during surgery, 55.1% thought they might become blind, 40.8% believed the surgery would be painful, and 8.2% followed religious practices that do not permit surgery. CONCLUSION: Some misconceptions were identified, and the fear of blindness was the most mentioned reason for not seeking cataract surgery, which indicates the need for orientation.